THE IMPACT OF CORPORATE SOCIAL RESPONSIBILITY ON TAX AGGRESSIVENESS - ferry irawan; Lukman Hakim Ahmad; Imam Muhasan (JURNAL MANAJEMEN DAN BISNIS, 2021)
In the last decade, national tax revenue experienced unperformed results. This situation led researchers to investigate factors affect it. One of the most discussed factors is tax aggressiveness. This study aims to explore how corporate social responsibility (CSR) influence firm’s tax aggressiveness. We used 54 manufacturing companies that listed in Indonesia Stock Exchange (IDX) for period 2012-2016. Using random effect, we obtained several findings. Tax aggressiveness behavior influenced by CSR characteristics and dimensions. Social and environment CSR activity has no impact on tax aggressiveness. In contrast, economic CSR activity significantly negative affect the firms’ behavior to apply tax aggressiveness.